المنهج وطريقة كشف الكلمات في معجم المنجد للويس معلوف - Shofwatul Fuadah (Fakultas Tarbiyah Universitas Ibrahimy, 2020)
Mu'jam almunjid is a famous mu'jam which is used by students in the world including muslim students in Indonesia. This mu’jam is considered as the most complete and comprehensive dictionary, because this is decorated with many pictures, colours and other advantages. So that many Islamic campuses and Islamic boarding schools around the world use this dictionary as the main dictionary. But the mu'jam which is used by many moslem students in this world was composed by two Catholic priests (rahib) named Fr. Louis Ma'luf al-Yassu’i and Fr. Bernard Tottel al-Yassu'i and was printed and distributed by a Catholic printing press since 1908. The use of the al-Munjid Dictionary, which has been used for a long time is not without opposition. Some ulama’ assume the dictionary is a part of an orientalist operation who have a hidden agenda to the Islamic world. Therefore, this study aims to present or peel the contents of the Al-Munjid dictionary by Louis Ma'luf. This study will focus on discussing the aspects of the definition, authors, purposes, methods, strengths and weaknesses and the opinions of scientists and scholars about this dictionary.